Private placements of equity and firm value : value enhancing or value destroying? - Kang, Jun-Koo (2022)
This paper reassesses two conflicting hypotheses on the valuation impacts of private placements of equity (PPEs), the monitoring/certification hypothesis and the managerial entrenchment hypothesis, by focusing on the shareholder approval, active buyer, and premium pricing features of PPEs. We find that PPEs with these features have significant positive announcement returns and insignificant mean long-run returns, while the corresponding announcement and long-run returns for PPEs without such features are significantly negative. Firms with value-enhancing PPE features are better governed and use proceeds more efficiently. Thus, the heterogeneous nature of PPEs helps reconcile the puzzling return patterns and conflicting hypotheses regarding PPEs.